PENGARUH PEMBERIAN BATUAN FOSFAT ALAM (BFA) DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays saccharata Sturt) KULTIVAR BONANZA F1 - Gunawan, Elvira Tiara; Budirokhman, Dodi; Wahyuni, Siti (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2025)
This study aims to determine the effect of giving natural rock phosphate (BFA) and chicken manure on the growth and yield of sweet corn (Zea mays saccharata Sturt) Bonanza F1 cultivar. The research was carried out in Kalisapu Village, Gunung Jati District, Cirebon Regency, from October to December 2021. The experimental design used was a factorial randomized block design (RAK). The treatment consisted of two factors which were repeated three times. The first factor is natural phosphate rock which consists of three levels, namely F1 = 250 kg/ha, F2 = 350 kg/ha, F3 = 450 kg/ha. While the second factor is chicken manure which consists of three levels, namely A1 = 5 tons/ha, A2 = 10 tons/ha, A3 = 15 tons/ha. Variables observed included plant height, number of leaves, stem diameter, root volume, ear diameter per plant, weight of cobs per plot and per plant, number of cobs per plot and per plant. The results showed that there was an interaction between the application of natural phosphate rock and chicken manure to the root volume of 42 DAP. Independent treatment of 350 kg/ha natural phosphate rock gave the best effect on stem diameter.